2021
DOI: 10.3390/v13091714
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Characterisation of a Highly Divergent Siadenovirus (Psittacine Siadenovirus F) from the Critically Endangered Orange-Bellied Parrot (Neophema chrysogaster)

Abstract: Siadenoviruses have been detected in wild and captive birds worldwide. Only nine siadenoviruses have been fully sequenced; however, partial sequences for 30 others, many of these from wild Australian birds, are also described. Some siadenoviruses, e.g., the turkey siadenovirus A, can cause disease; however, most cause subclinical infections. An example of a siadenovirus causing predominately subclinical infections is psittacine siadenovirus 2, proposed name psittacine siadenovirus F (PsSiAdV-F), which is enzoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 41 publications
2
29
0
Order By: Relevance
“…1 ) that is basal to all known avian siadenoviruses. This suggests that all the avian siadenoviruses evolved from the ancestral bird that gave rise to PsSiAdV-F, which is consistent with a recent study that reported that PsSiAdV-F was basal to all avian siadenoviruses 20 . Evidence that this ancestral species may have been a primitive Australian or African parrot includes the observation that PsSiAdV-F has only been detected in psittacine species where it causes predominantly subclinical infections.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…1 ) that is basal to all known avian siadenoviruses. This suggests that all the avian siadenoviruses evolved from the ancestral bird that gave rise to PsSiAdV-F, which is consistent with a recent study that reported that PsSiAdV-F was basal to all avian siadenoviruses 20 . Evidence that this ancestral species may have been a primitive Australian or African parrot includes the observation that PsSiAdV-F has only been detected in psittacine species where it causes predominantly subclinical infections.…”
Section: Discussionsupporting
confidence: 91%
“…The main aims of this study were not only to understand the virome structure of apparently healthy Australian Neophema birds but also to track the evolutionary history of a recently sequenced PsSiAdV-F in the critically endangered Australian parrot, the orange-bellied parrot ( Neophema chrysogaster ) 20 . Notably, the PsSiAdV-F sequenced from this study was very similar (a nucleotide identity of > 99% at genome level) to the recently sequenced two PsSiAdV-F strains of OBP2209 and WVL19065-01E from the orange-bellied parrot and African grey parrot ( Psittacus erithacus ), respectively, and phylogenetically all the three strains of PsSiAdV-F were positioned in a monophyletic subclade (100% bootstrap support ) (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations